2015
DOI: 10.1089/tmj.2014.0130
|View full text |Cite
|
Sign up to set email alerts
|

Tablet Computing in Clinical Training of Pediatric Residents

Abstract: The role of graduate medical education is changing with the introduction of new technologies. These technologies can differentially impact the various aspects of residency education and training. Residents reported using an iPad extensively in their clinical training. We argue that in addition to impacting traditional educational strategies, iPads can successfully facilitate aspects of clinical training in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…As argued by George, Dellasega, Whitehead, and Bordon (2013), adding an online social networking component targeting stress management can be an effective way for students in the health disciplines to manage stress. This work complements previous findings (Howard et al, 2015), which focused on the use of tablets in clinical training. The present outcomes concentrated on the academic aspects of graduate medical education.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As argued by George, Dellasega, Whitehead, and Bordon (2013), adding an online social networking component targeting stress management can be an effective way for students in the health disciplines to manage stress. This work complements previous findings (Howard et al, 2015), which focused on the use of tablets in clinical training. The present outcomes concentrated on the academic aspects of graduate medical education.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, it is clear the residents believe a tablet, such as the tablet, is an important technological tool for their future workplace. These findings are consistent with, and build upon, previous work (Howard, Coovert, Coovert, & Nelson, 2015) where physicians believe the use of a tablet will make them more efficient, organized, and collaborative.…”
Section: Transition To the Workplacesupporting
confidence: 90%
“…Studies have shown technologically-savvy residents benefit from apps in medical education. [6][7][8][9] Although research in the area of technology and orientation is nascent, it has been demonstrated that learners perceive the integration of mobile technology will potentially improve their knowledge acquisition, facilitate collaborations, and enhance their efficiency, 10,11 However some authors have warned of the distraction and privacy issues. 12 In this paper we report the usage trends for this app, including anticipated versus actual app utilization.…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that the medical apps ecosystem will continue to grow and develop substantially [1]. Furthermore, the future of healthcare computing is expected to become rooted in mobile technologies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%